KEWAJIBAN DAN TANGGUNG JAWAB HUKUM PERDATA DALAM PERLINDUNGAN PRIVASI DATA PASIEN DALAM LAYANAN KESEHATAN DIGITAL - SUMITRA, SYAMSUL; Yuyut Prayuti, Yuyut Prayuti; Arman Lany, Arman Lany (Jurnal Media Justitia Nusantara, 2024)
Civil legal obligations and responsibilities related to the protection of patient data in digital healthcare services that are increasingly popular in the contemporary medical world. The main aim of this article is to analyze the legal framework governing the protection of patient data privacy in the digital environment; identify civil law obligations governing digital health service providers to protect patient data; and analyze how patient rights and obligations relate to protecting patient data privacy in digital health services. Medical professional ethical guidelines and the Personal Data Protection Act are some of the relevant rules and regulations examined in this research. The results of this study show that there is variation in how patients manage the privacy of their data in digital health services; therefore, there is a need to increase legal knowledge and awareness of stakeholders, including healthcare providers, application developers, and patients.